1996
DOI: 10.1897/1551-5028(1996)015<0332:iceima>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cadmium Excretion in Metal-Adapted Populations of the Midge Chironomus Riparius (Diptera)

Abstract: Abstract-Cadmium kinetics were studied in cadmium-adapted and nonadapted field populations of the midge Chironomus riparius. Accumulation and elimination experiments were carried out using first-generation laboratory-reared animals. Differences between populations were, therefore, assumed to have a genetic basis. Larvae were dissected to analyze the guts and the remainder of the larvae separately. First-order one-compartment models were not always successful in describing accumulation processes, probably due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 37 publications
5
41
4
Order By: Relevance
“…In other studies, a decrease in metal accumulation contributes to a lower overall exposure. This has been observed in least killifish exposed to cadmium (Xie and Klerks 2004a), chironomids adapted to cadmium (Postma et al 1996), and mummichog embryos from mercury-exposed adults (Weis et al 1981). A single gene appears to be responsible for the intrinsic difference in cadmium resistance between BS90 and NMRI strains of B. glabrata exposed to toxic levels of cadmium (Salice and Roesijadi, 2002).…”
Section: Discussionmentioning
confidence: 93%
“…In other studies, a decrease in metal accumulation contributes to a lower overall exposure. This has been observed in least killifish exposed to cadmium (Xie and Klerks 2004a), chironomids adapted to cadmium (Postma et al 1996), and mummichog embryos from mercury-exposed adults (Weis et al 1981). A single gene appears to be responsible for the intrinsic difference in cadmium resistance between BS90 and NMRI strains of B. glabrata exposed to toxic levels of cadmium (Salice and Roesijadi, 2002).…”
Section: Discussionmentioning
confidence: 93%
“…However, the mechanisms for these adaptations are not clear. It was suggested that they excrete the metals (Postma et al, 1996;Groenendijk et al, 1999) or bind them with metal-binding proteins (Yamamura et al, 1983). Here we demonstrate that endogenous bacteria have a role in protecting the insect from pollutants.…”
Section: The Role Of Endogenous Bacteria In Chironomids Y Senderovichmentioning
confidence: 99%
“…Boisson et al 1998), reduced efficiency of assimilation from the diet, a higher rate constant of metal loss (e.g. Postma et al 1996), an enhanced rate of detoxification (Levinton et al 2003), or any combination of these. Selective pressure to reduce the potential of toxic action would result in genetically based changes in such physiological traits, corresponding to the selection of a metaltolerant population (Luoma 1977, Klerks & Weis 1987, Levinton et al 2003, Luoma & Rainbow 2008.…”
Section: Introductionmentioning
confidence: 99%